Exploring the relationship between burnout, learning engagement and academic self-efficacy among EFL learners: A structural equation modeling analysis - Cong, Yilin; Yang, Lei; Ergun, Anna Lia Proietti (ELSEVIER, 2024)
This study examined the role of learning engagement and academic self-efficacy in the feelings of burnout among English as a foreign language (EFL) students from China (N = 197). Three closed-ended scales were employed in the quantitative phase of this study to explore the relationship between the latent variables. Additionally, a hypothetical model was created and verified using Pearson's correlation analysis, structural equation modeling (SEM), path analysis, and mediating effect test. The investigation results demonstrated that while learning engagement was positively correlated with medium levels of academic self-efficacy, student burnout was inversely correlated with both variables. Among Chinese EFL students, academic self-efficacy and learning engagement are predictive of burnout, and learning engagement can act as a mediator to reduce the impact of academic self-efficacy on burnout. The implications for EFL teaching and learning are discussed in light of those findings, including enhancing EFL students' self-efficacy to reduce pessimism and increase academic achievement.
Keywords: EFL learners; Burnout; Learning engagement; Academic self -efficacy; UNIVERSITY-STUDENTS; POSITIVE PSYCHOLOGY; WORK ENGAGEMENT; EMOTIONS; CHINESE; ACHIEVEMENT; Psychology